Empowerment for Keliling Benteng Ulu Villages PKK Group in Overcoming Stunting to Achieve Nutrition Independent Village - Triawanti Triawanti; Didik Dwi Sanyoto; Dewi Rahayu; Gastin Gabriel Jangkang; Faradhiba Tantri Lemba; Muhammad Reyhan Firdaus; Tyas Ningrum Rahmadayanti (Lambung Mangkurat, 2023)
Stunting is a failure to achieve optimal growth measured by height per age (TB/U) categorized into short and very short. South Kalimantan has a prevalence of stunting under five according to SSGI data in 2021, which is 30.0 exceeding the national prevalence and is the 5th largest in Indonesia. This activity aims to increase public knowledge, especially PKK mothers about stunting and how to overcome it, as well as improve the skills of PKK mothers in the Keliling Benteng Ulu Village in processing local food ingredients into nutritious and economical food. The method used in this activity is the empowerment of the PKK group in the Keliling Village of Benteng Ulu in July 2022.This activity has three stages which include preparation, implementation, and evaluation of activities. Most (46%) of the participants are 20-30 years old who are still active and productive and the highest education level of the participants is elementary school at 46%. Most (54%) participants experienced an increase in knowledge. Overall, the participants agreed and strongly agreed that the CERDAS Pocket Book was interesting, useful, and increased the knowledge of the trainees. Most of the participants agreed and strongly agreed that this training activity was interesting and had benefits and the objectives were clear and the participants would try to process seluang pumpkin nuggets at home after the activity was over. The result of this training is that the processing of seluang pumpkin nuggets, empek-empek, pentol can be an alternative in preventing stunting in toddlers.